Pengetahuan Tradisional dalam Bercocok Tanam Padi Ladang pada Etnik Muna di Desa Labulu-Bulu Kecamatan Parigi Kabupaten Muna - Wa Ode Suharti; Akhmad Marhadi; Rahmat Sewa Suraya (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2022)
Farming rice fields in the Muna ethnic group is full of hidden knowledge but not all people understand this, so this study was written with the aim of identifying and describing traditional knowledge before and after planting rice fields in the Muna Ethnic in Labulu-Bulu Village, Parigi District, Muna Regency. This type of research data in the form of qualitative data provided by the informant. The results of this study indicate that Traditional Knowledge in upland rice cultivation is belief in site selection, ritual implementation, timing of planting, belief in geographical conditions or conditions, and understanding of farmers who usually cultivate field rice using traditional tools.